Literasi Digital sebagai Faktor Penentu Prestasi Akademik - Debi Wulandari; Khusaini Khusaini; Estu Niana Syamiya (Universitas Indraprasta PGRI Jakarta, 2022)
One indicator of teaching and learning success is the academic achievement of the students. There have been many efforts made by previous researchers and policymakers to help improve students' academic abilities, often with the development of digital technology today. The study aims at examining the influence of digital literacy and control variables on academic achievement. The sample size used as many as 134 students of SMA Negeri 5 Tangerang Regency and simple random sampling as a sampling technique. As for determining the sample size utilized the Krecjie & Morgan table (sampling error 10%). We distributed questionnaires using google forms through student WhatsApp groups and have been tested for validity and reliability. Analysis of the data used was descriptive causality. The author utilized a multiple linear regression model for his testing. The results showed that digital literacy contributes significantly to improving academic achievement. The higher the digital literacy of students, the more the average trend of academic achievement increases. The findings of this study contribute to science, particularly the field of education, and help students to have good attitudes, behaviors, and morals in utilizing digital developments both inside the school and outside the school.